NEW RULES ON CREDITWORTHINESS ASSESSMENT FOR FINANCIAL SERVICES USERS - Radović, Mirjana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2026)
This paper provides a detailed analysis of the rules introduced by the 2025 Law on the Protection of Financial Service Users, which regulate the assessment of the creditworthiness of financial service users. The first part of the paper is introductory in nature and contains an explanation of the concept of creditworthiness, considering its evolution from a subjective to an objective understanding. The second part presents the legislative approach to regulating creditworthiness assessment in Serbia from the adoption of the Law on Obligations to the present day. The third section examines the bank’s obligation to assess users’ creditworthiness, particularly focusing on changes to the scope of application of this obligation and how it is defined. The fourth section addresses the prohibition, introduced in the new law, that prevents banks from entering into credit services agreements with users who are not creditworthy. The fifth section analyses the legal position of a user whose creditworthiness assessment involved profiling. The final sixth part sets out the legal consequences of violating the new creditworthiness assessment rules from the perspectives of both banks and financial service users. Overall, the author concludes that the new law has improved the regulatory framework governing creditworthiness assessment, making this a significantly more important mechanism for consumer protection. However, numerous issues remain that require consistent interpretation and application.